Flag-Transitive 2-Designs and Mathieu Group M12 - Delu Tian; Zhilin Zhang; Yajie Wang (Journal of Mathematics)
In this paper, we announce the completion of the search for all flag-transitive point-primitive nontrivial 2-designs with M12 as the socle of their automorphism groups, and we discover that there are exactly nine of these nonisomorphic 2-designs. This paper enriches the classification of 2-designs and provides valuable references for addressing the classification of designs under the action of other simple groups.